Process trumps potential public good: better vaccine safety through linked cross‐jurisdictional immunisation data in Australia - Katherine M. Duszynski; Nicole L. Pratt; John W. Lynch; Annette Braunack‐Mayer; Lee K. Taylor; Jesia G. Berry; Vicki Xafis; Jim Buttery; Michael S. Gold; on behalf of the Vaccine Assessment Using Linked Data (VALiD) (Elsevier, 2019)
Abstract Objective: To provide insights into complexities of seeking access to state and federal cross‐jurisdictional data for linkage with the Australian Childhood Immunisation Register (ACIR). We provide recommendations for improving access and receipt of linked datasets involving Australian Government‐administered data. Methods: We describe requirements for linking eleven federal and state data sources to establish a national linked dataset for safety evaluation of vaccines. The required data linkage methodology for integrating cross‐jurisdictional data sources is also described. Results: Extensive negotiation was required with 18 different agencies for 21 separate authorisations and 12 ethics approvals. Three variations of the 'best practice' linkage model were implemented. Australian Government approval requests spanned nearly four years from initial request for data, with a further year before ACIR data transfer to the linkage agency. Conclusions: Integration of immunisation registers with other data collections is achievable in Australia but infeasible for routine and rapid identification of vaccine safety concerns. Lengthy authorisation requirements, convoluted disparate application processes and inconsistencies in data supplied all contribute to delayed data availability. Implications for public health: Delayed data access for safety surveillance prevents timely epidemiological reviews. Poor responsiveness to safety concerns may erode public confidence, compromising effectiveness of vaccination programs through reduced participation.